A new hypothesis on the manifestation of cerebral malaria: The secret is in the liver - Martins, Yuri Chaves (2013)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa em Malária. Centro de Pesquisa Diagnóstico e Treinamento em Malária. Rio de Janeiro, RJ, Brasil / Albert Einstein College of Medicine. Department of Pathology. The Bronx, NY, USA.